Difference between revisions of "In Section 2.2, one too many parentheses in an expression for y(t)"

From FBSwiki
Jump to: navigation, search
Line 8: Line 8:
 
|Page number=2-8
 
|Page number=2-8
 
|Line number=12
 
|Line number=12
|Current status=Submitted
+
|Current status=Pending
 
}}
 
}}
 
y(t) = P(s)*e^st – C(s)*P(s)*y(t), according to the block diagram Fig 2.4.
 
y(t) = P(s)*e^st – C(s)*P(s)*y(t), according to the block diagram Fig 2.4.

Revision as of 19:35, 31 January 2017

Edition Second
Version number 3.0h
Submission date 4 Oct 2016
Your name Kai Kirk
E-mail address mailto:kkirk@caltech.edu
Chapter 2
Page number 2-8
Line number 12
Current status Pending

y(t) = P(s)*e^st – C(s)*P(s)*y(t), according to the block diagram Fig 2.4.

Currently the expression is y(t) = P(s)* (e^st – C(s)*P(s)*y(t)) = P(s)*e^st – C(s)*y(t)*P(s)^2

21 Nov 16, RMM: reported multiple times. Chanud reported on 1 Oct, but Kirk gave a better fix.